Two new Stauroneis species (Bacillariophyta, Stauroneidaceae) from midwestern karstic Brazilian formations - Tusset, Eduardo A.; Tremarin, Priscila I.; Ludwig, Thelma A.v. (Phytotaxa, 2018)
The morphology of three Stauroneis species from midwestern karstic Brazilian formations was illustrated under light and electron microscopy. Two new Stauroneis are described and compared with similar species in the genus. Stauroneis cavalcantei Tremarin, Tusset & T. Ludwig is characterized by lanceolate valves with subtly protracted apices, and S. karstica Tusset, Tremarin & T. Ludwig by rhombic-lanceolate valves with attenuate to acutely-rounded apices, reduced pseudosepta, bow-tie-shaped stauros, and areolae depressed along prominent longitudinal-oriented apical ribs. Stauroneis alabamae is a scarcely known species and unprecedented scanning electron microscopy illustrations are provided.